2014
DOI: 10.1371/journal.pone.0102632
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Cognitive Reserve in Healthy Adults Using the Cognitive Reserve Scale

Abstract: The concept of cognitive reserve emerged from observed disparities between brain pathology and clinical symptoms. It may explain better neuropsychological performance in healthy individuals. The objectives of this study were to measure reserve in healthy subjects using a new Cognitive Reserve Scale (CRS), analyze the internal consistency of the CRS, and analyze validity evidence. A total of 117 healthy individuals were divided into two groups: 87 adults (aged 18–64 years) and 30 elderly adults (≥65 years). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 62 publications
4
72
1
4
Order By: Relevance
“…Many similar questionnaires have been introduced in the last few years [22-25] but the CRIq, which we used in our study, is unique in that it takes into account the frequency and time spent in each recorded activity (educational, occupational, or leisure time). Thus, the CRI illustrates active, continuous, and lifelong CR formation.…”
Section: Discussionmentioning
confidence: 99%
“…Many similar questionnaires have been introduced in the last few years [22-25] but the CRIq, which we used in our study, is unique in that it takes into account the frequency and time spent in each recorded activity (educational, occupational, or leisure time). Thus, the CRI illustrates active, continuous, and lifelong CR formation.…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses incorporating studies up to 2004 suggested that the risk of dementia is decreased by 46% in people with high cognitive reserve defined by these parameters [13,14]. Consequently questionnaires capturing these facets of life experience were developed as measures of cognitive reserve [15][16][17][18]. Such tools are useful as they provide a methodology for the uniform collection of pertinent variables across studies.…”
Section: Measuring Cognitive Reservementioning
confidence: 99%
“…The psychometric properties of the CRS suggest its adequacy to measure cognitive reserve (León et al, 2014).…”
Section: Cognitive Reserve Scalementioning
confidence: 99%
“…First, a review of cognitive reserve studies was conducted to generate the items of the scale, and the CRS was supervised by experts (León et al, 2011). Secondly, the relationships between the CRS score and educational attainment, occupational attainment and IQ, three variables usually used as proxies of cognitive reserve (León et al, 2014), were analysed. The results showed that educational attainment affected the CRS score (p = .004, partial η 2 = .07), and that neither occupational attainment (p = .898) nor IQ (p = .33) affected the CRS score.…”
Section: Cognitive Reserve Scalementioning
confidence: 99%
See 1 more Smart Citation